High resolution depth distribution of Bacteria, Archaea, methanotrophs, and methanogens in the bulk and rhizosphere soils of a flooded rice paddy - Lee, Hyo Jung; Jeong, Sang Eun; Kim, Pil Joo; Madsen, Eugene L.; Jeon, Che Ok (Frontiers in Microbiology, 2015)
The communities and abundances of methanotrophs and methanogens, along with the oxygen, methane, and total organic carbon (TOC) concentrations, were investigated along a depth gradient in a flooded rice paddy. Broad patterns in vertical profiles of oxygen, methane, TOC, and microbial abundances were similar in the bulk and rhizosphere soils, though methane and TOC concentrations and 16S rRNA gene copies were clearly higher in the rhizosphere soil than in the bulk soil. Oxygen concentrations decreased sharply to below detection limits at the 8 mm depth. Pyrosequencing of 16S rRNA genes showed that bacterial and archaeal communities varied according to the oxic, oxic-anoxic, and anoxic zones, indicating that oxygen is a determining factor for the distribution of bacterial and archaeal communities. Aerobic methanotrophs were maximally observed near the oxic-anoxic interface, while methane, TOC, and methanogens were highest in the rhizosphere soil at 30–200 mm depth, suggesting that methane is produced mainly from organic carbon derived from rice plants and is metabolized aerobically. The relative abundances of type I methanotrophs such as Methylococcus, Methylomonas, and Methylocaldum decreased more drastically than those of type II methanotrophs (such as Methylocystis and Methylosinus) with increasing depth. Methanosaeta and Methanoregula were predominant methanogens at all depths, and the relative abundances of Methanosaeta, Methanoregula, and Methanosphaerula, and GOM_Arc_I increased with increasing depth. Based on contrasts between absolute abundances of methanogens and methanotrophs at depths sampled across rhizosphere and bulk soils (especially millimeter-scale slices at the surface), we have identified populations of methanogens (Methanosaeta, Methanoregula, Methanocella, Methanobacterium, and Methanosphaerula) and methanotrophs (Methylosarcina, Methylococcus, Methylosinus, and unclassified Methylocystaceae) that are likely physiologically active in situ.